2006
DOI: 10.1021/bc060125e
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific, Covalent Attachment of Proteins to a Solid Surface

Abstract: Immobilized and site-specifically labeled proteins are becoming invaluable tools in proteomics. Here, we describe a strategy to attach a desired protein to a solid surface in a covalent, site-specific manner. This approach employs an enzymatic posttranslational modification method to site-specifically label a target protein with an azide; an alternative substrate for protein farnesyl transferase containing an azide group was developed for this purpose. A bio-orthogonal Cu(I)-catalyzed cycloaddition reaction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
132
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 44 publications
0
132
0
2
Order By: Relevance
“…The convective mass transfer process can accelerate the diffusion of compounds, especially biopolymers, to access the monolith surface. Covalent immobilization of enzyme on a capillary monolithic column is an useful method to prepare enzyme microreactor, e.g., immobilization by genetic engineering [24], Staudinger ligation reaction [25], or azide-alkyne click reaction [26]. The immobilized trypsin microreactor by coupling with RPLC-MS/MS, CE and CE-MS has been applied for analysis of proteins and peptides [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The convective mass transfer process can accelerate the diffusion of compounds, especially biopolymers, to access the monolith surface. Covalent immobilization of enzyme on a capillary monolithic column is an useful method to prepare enzyme microreactor, e.g., immobilization by genetic engineering [24], Staudinger ligation reaction [25], or azide-alkyne click reaction [26]. The immobilized trypsin microreactor by coupling with RPLC-MS/MS, CE and CE-MS has been applied for analysis of proteins and peptides [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…[46] On the other hand, the Huisgen 1,3-dipolar cycloaddition reaction was used in a novel strategy for covalent attachment of desired proteins to solid surfaces. [47] Azides were attached to the protein via enzymatic posttranslational modification at the C-terminus, which then enabled further immobilization onto alkyne-functionalized agarose beads. In addition, the Huisgen cycloaddition reaction was employed for the development of an efficient system for the immobilization of complex azide-saccharides to microtiter plates via lipid alkyne tethers.…”
Section: Role Of Click Chemistry In Surface Engineeringmentioning
confidence: 99%
“…The copolymer p(LA-co-MPC) was electrospun into continuous fibers with a regular average diameter of ca 2-4 mm. In parallel, Testisspecific protease 50 (TSP50), a breast cancer sensitive protease, was non-specifically functionalized with azide groups [110][111][112] and subjected to a copper (I) catalyzed click chemistry cycloaddition with the p(LA-co-MPC) copolymer. The TSP50-immobilized fibers were successively incubated with anti-TSP50 antigen and then with HRP-Ig.…”
Section: Glycoconjugatesmentioning
confidence: 99%
“…A general method for the site-specific covalent conjugation of proteins onto agarose gels was reported by Distefano and coworkers. [111] This approach employed initially an enzymatic post-translational modification method to site-specifically label a target protein with an azide, which was followed by a bioorthogonal Cu(I)-catalyzed cycloaddition reaction to covalently attach the protein to agarose and beads bearing alkyne functional group. It is important to note that in this study it was also demonstrated that the click capture step could be efficiently performed on both purified and complex protein mixtures.…”
Section: Glycoconjugatesmentioning
confidence: 99%